TELAAH AYAT-AYAT BERBASIS MANAJEMEN PENDIDIKAN DALAM AL-QUR’AN - Adhe Mantika, Nurul (Jurnal El-Hikam, 2022)
Studies on the issue of Islamic education have given birth to dynamics and scientific paradigms, especially in Islamic education thought leaders. In particular, Islamic education has been the main focus of how Islamic education should be developed optimally, especially in developing Islamic education management. If examined based on the Qur'an, it has been able to respond to today's problems and happenings, namely how the Qur'an should talk about the issue of Islamic education management so that education should be developed according to what is expected. This has become an academic anxiety. The author tries to examine the verses of the Qur'an based on Islamic education management, then the author examines the approach to the study of tahilili interpretation, namely by examining the verses of the Qur'an in an analytical descriptive manner. The focus of this research is to examine the verses of the Qur'an based on Islamic education management in the tahlili interpretation approach. Specifically, the presence of the Qur'an is essentially an effort to make a reference knife in various aspects of study. One of them is the Qur'an that regulates the pattern of life universally. So that in the Qur'an, management is essentially to develop, shape, educate, according to what has been planned. As in the Qur'an in general that, education is the location of character formation to realize Islamic education based on Insan al-Kamil, namely plenary by developing the study of Islamic education management.